Chemical evolution of 26Al and 60Fe in the Milky Way. Issue 3 (21st October 2022) - Vasini, A; Matteucci, F; Spitoni, E
ABSTRACT: We present theoretical mass estimates of 26 Al and 60 Fe throughout the Galaxy, performed with a numerical chemical evolution model including detailed nucleosynthesis prescriptions for stable and radioactive nuclides. We compared the results for several sets of stellar yields taken from the literature, for massive, low and intermediate mass stars, nova systems (only for 26 Al) and supernovae Type Ia. We then computed the total masses of 26 Al and 60 Fe in the Galaxy. We studied the bulge and the disc of the Galaxy in a Galactocentric radius range of 0–22 kpc. We assumed that the bulge region (within 2 kpc) evolved quickly suffering a strong star formation burst, while the disc formed more slowly and inside–out. We compared our results with the 26 Al mass observed by the gamma-ray surveys COMPTEL and INTEGRAL to select the best model. Concerning 60 Fe, we do not have any observed mass value so we just performed a theoretical prediction for future observations. In conclusion, low, intermediate mass stars, and Type Ia supernovae contribute negligibly to the two isotopes, while massive stars are the dominant source. The nova contribution is, however, necessary to reproduce the observations of 26 Al. Our best model predicts 2.12 M⊙ of 26 Al, in agreement with observations, while for 60 Fe our best mass estimate is ∼1.05 M⊙ . We also predicted the present injection rate of 26 Al and 60 Fe in the Galaxy and compared it with previous results, and we found a larger present time injection rate along the disc.